"XI SHUAI" 蟋蟀 ("CRICKET") AND ITS CONSEQUENCES: ISSUES IN EARLY CHINESE POETRY AND TEXTUAL STUDIES. (September 2019) - Kern, Martin
Abstract: The present article explores questions about the composition, performance, circulation, and transmission of early Chinese poetry by examining a small number of poems from the received Mao shi and their counterparts in recently discovered manuscripts. Starting from a close examination of the poem "Xi shuai" ("Cricket"), the essay briefly discusses the problems we face in dealing with looted manuscripts before advancing toward rethinking the patterns of early Chinese poetic composition and transmission. Instead of taking individual poems as discrete, reified objects in the form we encounter them in the Mao shi, it is suggested to read them as particular instantiations of circumscribed repertoires where the individual poetic text is but one of many realizations of a shared body of ideas and expressions. This analysis is informed by the examination of both manuscript texts and the received literature, but also by comparative perspectives gained from both medieval Chinese literature and other ancient and medieval literary traditions. In emphasizing the formation of poetry as a continuous process, it leaves behind notions of "the original text, " authorship, and the moment of "original composition"—notions that held no prominence in the early Chinese literary tradition before the empire. 提要: 通過檢視部分傳世《毛詩》內容及其在近年所見出土文獻中的對應篇章，本文探究了關於早期中國詩歌成篇、表演、流通以及傳的問題。以對《蟋蟀》詩的細緻考察為起點，本文簡要討論了我們在處理盜掘寫本文獻時所面對的諸種問題，進而重新思考早期中國詩歌的成篇和傳播模式。學界通常將各首詩歌視為彼此分離且具象化的個體、以《毛詩》中所見的那種形式存在，與此立場不同，本文建議將它們視作有限素材庫的諸種特定實現。在這些素材庫中，作為個體的詩歌文本僅僅是某個包含多種理念和表達之共享整體的諸多具體實現之一。這一分析源自於對寫本文獻和傳世文獻的雙向考察，也得益於在中國中古文學與其它早期及中古文學傳統之間建立起的比較性視野。通過將詩歌形成強調為一種持續性過程，本文摒棄了諸如"原本"、"作者"以及"原作"時刻的概念，這些概念在前帝國時代的早期中國文學傳統中並不重要。